Thomas Aquinas and William E. Carroll on Creatio ex Nihilo: A Response to Joseph Hannon's "Theological Objections to a Metaphysicalist Interpretation of Creation". Issue 2 (3rd April 2021) - Silva, Ignacio
ABSTRACT: Joseph Hannon has expressed a most surprising objection to Aquinas scholar Prof William E. Carroll in his latest paper "Theological Objections to a Metaphysicalist Interpretation of Creation." The main claim is that Prof. Carroll misunderstands Aquinas' doctrine of creatio ex nihilo by reducing it to a metaphysical notion, rather than considering it in its full theological sense. In this paper I show Hannon's misinterpretation of Carroll's and Thomas Aquinas' thought, particularly by stressing the dependence that the doctrine of providence through secondary causes has on the doctrine of creatio ex nihilo .